The Role of Sphingolipid Metabolism in Bone Remodeling - Qi, Tang; Li, Liao; Weidong, Tian (Frontiers in Cell and Developmental Biology, 2021)
Emerging studies of bioactive lipids have made many exciting new discoveries in recent years, and sphingolipids and their metabolites perform a vast variety of cellular functions beyond what was previously believed. The use of genetically manipulated mouse models, gene and protein discovery have allowed us to obtain new insights into the role of sphingolipid played on skeletal remodeling. This review summarizes studies or understandings of the cross-talk between sphingomyelin, ceramide, and S1P of sphingolipids family and the cells, especially osteoblasts and osteoclasts of the bone through which bone is constantly remodeled during life. This review also shows agonists and antagonist of S1P as possible therapeutic options and opportunities on bone diseases.